"What Is the Point of Parliamentary Debate?" Deliberation, Oratory, Opposition and Spectacle in the British House of Commons. (1st April 2017) - Finlayson, Alan
Abstract : This article seeks to open up debate about Parliamentary debate by exploring the history of ideas about Parliamentary debate and rhetoric through the lens of four core concepts: deliberation, oratory, opposition and spectacle. These are not the names of singular ideas let alone schools of thought; they are conceptual fields each of which gives a particular shape to ways of conceiving, criticizing and defending Commons debate. In mapping this topos – identifying historical debates and practices alongside contemporary arguments found in political theory, political science and Rhetoric – I show that our thinking and arguing about the Commons is part of a contested and ongoing history more complex than we acknowledge. I argue that Parliamentary Debate has a number of purposes and that our thinking about it, and evaluation of it, should not be contained within the frame of "deliberation" but should also take account of the political value and importance of oratory, opposition and spectacle.